Impact of the International Nosocomial Infection Control Consortium's multidimensional approach on rates of ventilator-associated pneumonia in 14 intensive care units in 11 hospitals of 5 cities within Argentina - Rosenthal, Victor Daniel (2018)
Background: To analyze the impact of the International Nosocomial Infection Control Consortium (INICC) multidimensional approach (IMA) on ventilator-associated pneumonia (VAP) rates in 11 hospitals within 5 cities of Argentina from January 2014-April 2017. Methods: A multicenter, prospective, before–after surveillance study was conducted through the use of International Nosocomial Infection Control Consortium Surveillance Online System. During baseline, we performed outcome surveillance of VAP applying the definitions of the Centers for Disease Control andPrevention's National Healthcare Safety Network. During intervention, we implemented the IMA, which included a bundle of infection prevention practice interventions, education, outcome surveillance, process surveillance, feedback on VAP rates and consequences, and performance feedback of process surveillance. Bivariate and multivariate regression analyses were performed using a logistic regression model to estimate the effect of the intervention. Results: We recorded 3,940 patients admitted to 14 intensive care units. At baseline, there were 19.9 VAPs per 1,000 mechanical ventilator (MV)-days—with 2,920 MV-days and 58 VAPs, which was reduced during intervention to 9.4 VAPs per 1,000 MV-days—with 9,261 MV-days and 103 VAPs. This accounted for a 52% rate reduction (incidence density rate, 0.48; 95% confidence interval, 0.3-0.7; P.001). Conclusions: Implementing the IMA was associated with significant reductions in VAP rates in intensive care units within Argentina.